2014
DOI: 10.1186/1742-9994-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Are ticks venomous animals?

Abstract: IntroductionAs an ecological adaptation venoms have evolved independently in several species of Metazoa. As haematophagous arthropods ticks are mainly considered as ectoparasites due to directly feeding on the skin of animal hosts. Ticks are of major importance since they serve as vectors for several diseases affecting humans and livestock animals. Ticks are rarely considered as venomous animals despite that tick saliva contains several protein families present in venomous taxa and that many Ixodida genera can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 157 publications
2
49
0
1
Order By: Relevance
“…As such, the α-gal syndrome represents a potentially fertile area for discovery of mediators and pathways that govern type 2 immunity, an area of immunology that remains enigmatic. This premise would also be compatible with an emerging literature describing a protective role for type 2 immunity against venomous organisms, which arguably ticks represent [5456]. …”
Section: Resultssupporting
confidence: 78%
“…As such, the α-gal syndrome represents a potentially fertile area for discovery of mediators and pathways that govern type 2 immunity, an area of immunology that remains enigmatic. This premise would also be compatible with an emerging literature describing a protective role for type 2 immunity against venomous organisms, which arguably ticks represent [5456]. …”
Section: Resultssupporting
confidence: 78%
“…Ticks are specialized hematophagous ectoparasites of significant medical and public health importance (RANDOLPH, 2009). During the penetration process of the host skin, ticks succeed in blood feeding by manipulating the host's hemostatic, inflammatory, and immune defense mechanisms, due to numerous active components with pharmacological applications (CABEZAS-CRUZ & VALDÉS, 2014;RADULOVIC et al, 2014;STIBRANIOVA et al, 2013). As a source of anti-neoplasic compounds, it has been reported that tick saliva constituents can affect cancer cell proliferation (KAZIMIROVA et al, 2006), apoptosis (AKAGI et al, 2012, migration and invasion (POOLE et al, 2013), and tumor growth and angiogenesis (CARNEIRO-LOBO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One tick salivary substance that interferes with blood clotting is called Kunitz peptide. Kunitz peptides are small molecules that are also secreted by venomous organisms, such as scorpions and spiders, and they are an important component of tick saliva [4]. Tick salivary Kunitz peptides interfere with blood clotting, allowing the tick to slurp up its blood meal.…”
Section: Tick Saliva As Camouflagementioning
confidence: 99%